Do Active Labor Market Policies Help Unemployed Workers to Find and Keep Regular Jobs? - Jan C. van Ours (Institute for the Study of Labor (IZA), 2000)
This paper uses an administrative dataset to analyze to what extent active labor market policies in the Slovak Republic have been beneficial for unemployed workers. The focus is on two types of temporary subsidized jobs and on training. Short-term subsidized jobs seem to be the most efficient active labor market policy. Workers that are or have been on a shortterm subsidized job have a higher job finding rate than other unemployed workers have and once they find a job they have a lower job separation rate than workers that have not been on a short-term subsidized job. Long-term subsidized jobs have a negative effect on the job finding rate and no effect on the job separation rate. The positive effect of training on the job finding rate of unemployed workers may have to do with reversed causality: some workers enter a training program only after they are promised a job. Training does not seem to affect the job separation rate.
Keywords: C41; J64; 330; Unemployment; active labor market policy; duration models; Arbeitsmarktpolitik; Arbeitslosigkeit; Slowakei